Pengaruh Inovasi dan Kompetensi Kewirausahaan Terhadap Keberhasilan Usaha Pada Usaha Angkringan Kecamatan Teluk Jambe Timur Kabupaten Karawang - Fauzi, Muhamad; Musadad, Anwar (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to test and analyze the Influence of Innovation and Entrepreneurial Competence on Business Success in Angkringan Businesses in East Telukjambe, Karawang Regency. The study was conducted using a quantitative verification method. To examine this influence, a range of scales and multiple linear regression analysis were used through the SPSS 25 tool. Samples were collected using the Isaac and Michael method and probability sampling techniques with propotionate stratified random sampling with a sample size of 103 samples from a population of 140 angkringan businesses. Based on the results of the analysis that has been carried out, this study proves that the determination coefficient between the Innovation and Entrepreneurial Competence variables obtained a value of 0.689 indicating that around 68.9% of the variation in business success (Y) can be explained by two independent variables, namely innovation (X1) and competence (X2). This means that these two variables have a significant influence on business success. Meanwhile, the remaining 31.1% of the variation in business success is influenced by other factors not included in this model or study.